2014
DOI: 10.3345/kjp.2014.57.10.434
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in the treatment of pediatric acute leukemia and brain tumor - continuous efforts for 100% cure

Abstract: Treatment outcomes of pediatric cancers have improved greatly with the development of improved treatment protocols, new drugs, and better supportive measures, resulting in overall survival rates greater than 70%. Survival rates are highest in acute lymphoblastic leukemia, reaching more than 90%, owing to risk-based treatment through multicenter clinical trials and protocols developed to prevent central nervous system relapse and testicular relapse in boys. New drugs including clofarabine and nelarabine are cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Technol. v.61: e18161278 2018 role during the fetus´s life and they may be the basis of cell communication that coordinates mother-fetus interactions while modulating the functional adaptability for extra-uterine life during the perinatal period [25][26] . Early studies [27] have demonstrated sexual differentiation in SYT cavies and possible masculinization in female genital organs.…”
Section: Discussionmentioning
confidence: 99%
“…Technol. v.61: e18161278 2018 role during the fetus´s life and they may be the basis of cell communication that coordinates mother-fetus interactions while modulating the functional adaptability for extra-uterine life during the perinatal period [25][26] . Early studies [27] have demonstrated sexual differentiation in SYT cavies and possible masculinization in female genital organs.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of this pathology in conventional protocols use isolated or combined 4 - 6 . antineoplastic drugs, radiotherapy and surgery according to the type 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In new pediatric ALL cases, use of modern treatment strategies such as improved risk stratification based on prognostic factors, newer treatment modalities, and adjustments in treatment regimen intensities have resulted in a 5-year event-free survival rate of approximately 80%, and 5-year survival rate approaching 90%, one of the highest in any pediatric cancers in developed nations [6,7]. However, 15%-20% of patients with pediatric ALL experience relapse during or after the first treatment [8,9].…”
Section: Introductionmentioning
confidence: 99%